Factor that influence to use Sport Facilities at Kota Kinabalu area in Yayasan Sabah Group toward the publics / Izzi Redzha Azuan Mohd Yacob - Mohd Yacob, Izzi Redzha Azuan (2013)
According to Yayasan Sabah Group (YSG), it was inception since 1966 where carries out three strategies to meet its mission by providing education, educational facilities, creating opportunities for a more equitable distribution of wealth and providing aids to charitable institutions and victims of natural disasters for the people of Sabah.